2017
DOI: 10.1016/j.jaci.2016.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of immediate hypothermia and leukocyte infiltration in an adjuvant-free mouse model of anaphylaxis

Abstract: Background Conflicting results have been obtained regarding roles of Fc receptors and effector cells in models of active systemic anaphylaxis (ASA). In part, this might reflect the choice of adjuvant used during sensitization, as various adjuvants might differentially influence the production of particular antibody isotypes. Objective We developed an ‘adjuvant-free’ mouse model of ASA and assessed the contributions of components of the ‘classical’ and ‘alternative’ pathways in this model. Methods Mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 68 publications
0
36
0
Order By: Relevance
“…101 Studies in mice have shown that depletion of monocytes/macrophages using clodronate liposomes can reduce anaphylaxis in both IgG-mediated passive models and active models 52, 89, 92, 102, 103 (Table 1). These data suggest that monocytes/macrophages might play an important role in anaphylaxis.…”
Section: Potential Effector Cells Of Anaphylaxismentioning
confidence: 99%
See 3 more Smart Citations
“…101 Studies in mice have shown that depletion of monocytes/macrophages using clodronate liposomes can reduce anaphylaxis in both IgG-mediated passive models and active models 52, 89, 92, 102, 103 (Table 1). These data suggest that monocytes/macrophages might play an important role in anaphylaxis.…”
Section: Potential Effector Cells Of Anaphylaxismentioning
confidence: 99%
“…52, 55 Antibody-mediated neutrophil depletion can reduce anaphylaxis in IgG-mediated PSA 52, 53, 56 and mast cell-independent ASA models. 53, 103 However, neutrophil-depleting antibodies had no effect in a mast cell-dependent ASA model induced without artificial adjuvants. 103 This suggests that neutrophils may be particularly prominent in ASA models induced with adjuvants and that such models may not require any non-redundant contributions of mast cells (Table 1).…”
Section: Potential Effector Cells Of Anaphylaxismentioning
confidence: 99%
See 2 more Smart Citations
“…Knockout models indicated that the anaphylactic drop of body temperature depended on mouse FcεRI, FcγRIII and γ-chain FcRγ, whereas FcγRIV related to inflammation only [65 ▪ ]. In this model, macrophages and neutrophils turned out to be less important in anaphylaxis than mast cells.…”
Section: Introductionmentioning
confidence: 99%